Clinical and demographic profile of cancer patients in a consultation-liaison psychiatric service - Citero, Vanessa de Albuquerque; Nogueira-Martins, Luiz Antonio; Lourenço, Maria Teresa; Andreoli, Sergio Baxter (São Paulo Medical Journal, 2003)
CONTEXT: An almost 50% prevalence of psychiatric disorders among cancer patients has prompted a series of studies on consultation-liaison psychiatry. Nonetheless, there are few reports on the epidemiological factors involving comorbidity between cancer and psychiatric disorders. OBJECTIVE: To evaluate the epidemiological profile of cancer inpatients referred to the consultationliaison psychiatric service in an oncology hospital during its first year of activity. TYPE OF STUDY: Descriptive study. SETTING: Tertiary-care teaching hospital. PARTICIPANTS: 319 patients referred 412 times to the consultation-liaison psychiatry service. PROCEDURES: From August 97 to July 98, an appraisal was made of data on all admissions registered at the Hospital do Câncer, and also all referrals registered at the consultation-liaison psychiatry service. MAIN MEASUREMENTS: The demographics and patients’ clinical data, the type and flow of the request, and the evaluation conducted by the service were analyzed and comparisons with the hospital data were made. The distribution of the number of referrals was used to construct a profile of patients who had repeatedly used the service. RESULTS: Psychiatric diagnoses were found in 59% of the cases. Forty-three percent of these required medication, 18.3% needed psychotherapy, 22.1% family intervention and 20.5% guidance from the staff. Over 22.8% of the consultations were reevaluations, mainly involving younger male patients with worst prognoses. These patients required lengthier and more elaborate intervention, and had higher prevalence of depressive and behavioral disorders. CONCLUSION: A younger and mainly male population of non-surgical oncological cases was referred to the consultation-liaison psychiatric service during its first year of activity. The psychiatric disorder prevalence was higher than expected, and consisted predominantly of mood disorders. We detected a priority group, namely the reevaluated patients, who deserved special attention throughout the psychiatric interventions.